Avaliação ambiental, caracterização da qualidade de água e transporte de sedimentos da bacia hidrográfica do Ribeirão Monjolo Grande (SP) - Spatti Junior, Eder Paulo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The pressure on natural resources, especially on water resources has increased significantly as is increased demand for space, reflecting the increasing degradation of water sources in different scales. Thus, it is of great value to perform work that can support the planning and subsequent management of natural resources with a view to environmental sustainability. In this context, this work performs the environmental assessment, characterization of water quality and sediment transport in the Monjolo Grande watershed, located in Ipeúna (SP). The simplified environmental evaluation indicated that while the area is totally rural environment, with 50% of the 20 points classified as high environmental impacts, causing great loss of vegetation and maintenance of erosion. The water quality evaluated the variation of physicochemical parameters, the concentration of major cations and anions, the suspended solids (particulate and dissolved), and total and dissolved concentrations of Al, Fe, Mn, Ba, Pb, Cu, Zi, Ni and Cd. The water quality evaluated the variation of physicochemical parameters, the concentration of major cations and anions, the suspended solids (particulate and dissolved) in addition to the concentration of Al, Fe, Mn, Ba, Pb, Cu, Zi, Ni and Cd. Such quantification framed the surface waters of the Monjolo Grande as Class 2, according to the CONAMA resolution 357. The transport of sediment showed a removal of 476 ton/km²/year, and the method of Colby indicated that most sediment is transported by drag, by the characteristics of the sediments, predominantly in the sand fraction

A pressão exercida sobre os recursos naturais, em especial sobre os recursos hídricos, tem aumentado de maneira significativa à medida que ocorre o aumento da demanda por espaço, refletindo na crescente degradação dos mananciais nas mais diferentes escalas. Dessa forma, torna-se de grande valia a execução de trabalhos de caráter técnico científico que possam subsidiar o planejamento e a consequente gestão desses recursos naturais com vistas à sustentabilidade ambiental. Nesse contexto, este trabalho realizou a avaliação ambiental, a caracterização da qualidade da água e o transporte de sedimentos na bacia hidrográfica do Ribeirão Monjolo Grande, localizada no município de Ipeúna (SP). A avaliação ambiental simplificada indicou que apesar da área encontrar-se totalmente em ambiente rural, 50% dos 20 pontos avaliados apresentam impactos ambientais classificados como altos ou preocupantes acarretados pelo mau uso da terra, ocasionando grande perda de vegetação e a manutenção de processos erosivos. A qualidade das águas avaliou a variação dos parâmetros físicoquímicos, a concentração dos principais cátions e anions, dos sólidos em suspensão (particulados e dissolvidos), e a concentração total e dissolvida de Al, Fe, Mn, Ba, Pb, Cu, Zi, Ni e Cd. Tal quantificação enquadrou as águas do Ribeirão Monjolo Grande na Classe 2 de acordo com a resolução CONAMA 357. O transporte de sedimentos indicou uma remoção de 476 toneladas/km²/ano e, a aplicação do método de Colby indicou que a maior parte dos sedimentos é transportada por arrasto no fundo do canal, dada a característica dos sedimentos, predominantemente na fração areia
Simplified environmental evaluation, characterization of water quality and sediment transport in the Monjolo Grande Watershed (SP)
Keywords: Geomorphology; Geomorfologia; Bacias hidrograficas; Água - Qualidade; Sedimentos (Geologia); Avaliação paisagística; Monjolo Grande, Ribeirão, Ipeúna (SP)